2020
DOI: 10.3389/fvets.2020.561592
|View full text |Cite
|
Sign up to set email alerts
|

Regional and Local Temporal Trends of Borrelia burgdorferi and Anaplasma spp. Seroprevalence in Domestic Dogs: Contiguous United States 2013–2019

Abstract: In 2019, in the United States, over 220,000 and 350,000 dogs tested positive for exposure to Anaplasma spp. and Borrelia burgdorferi, respectively. To evaluate regional and local temporal trends of pathogen exposure we used a Bayesian spatio-temporal binomial regression model, analyzing serologic test results for these pathogens from January 2013 to December 2019. Regional trends were not static over time, but rather increased within and beyond the borders of historically endemic regions. Increased seroprevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 68 publications
1
15
0
Order By: Relevance
“…In the USA, over 100,000 and 220,000 dogs were seropositive to Anaplasma spp. in 2015 and 2019, respectively ( 248 , 249 ). Two recent studies analyzing regional trends of Anaplasma spp.…”
Section: Distribution and Prevalence Of Anaplasma Phagocytophilummentioning
confidence: 99%
See 2 more Smart Citations
“…In the USA, over 100,000 and 220,000 dogs were seropositive to Anaplasma spp. in 2015 and 2019, respectively ( 248 , 249 ). Two recent studies analyzing regional trends of Anaplasma spp.…”
Section: Distribution and Prevalence Of Anaplasma Phagocytophilummentioning
confidence: 99%
“…Two recent studies analyzing regional trends of Anaplasma spp. exposure in dogs showed that seroprevalence increased broadly in the northeastern, upper midwestern states, northern California, mid-atlantic coast and southern Oregon ( 249 , 250 ). In Canada, six serologic surveys on Anaplasma spp.…”
Section: Distribution and Prevalence Of Anaplasma Phagocytophilummentioning
confidence: 99%
See 1 more Smart Citation
“…For zoonotic pathogens, dogs may serve as effective sentinels ( 78 , 79 ). For example, seroprevalence of Borrelia burgdorferi in dogs may be a sensitive marker of human risk for Lyme disease as dogs are infected at a higher frequency ( 80 , 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…These spillover events have occurred even in areas far from urban centers with large populations of domestic animals, such as Bolivia’s Kaa-Iya del Gran Chaco and Noel Kempff Mercado National Parks [ 18 , 20 ]. Domestic dogs and cats can also serve as sentinels to detect the circulation of important pathogens, including some that are of zoonotic concern [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Currently, there is little understanding of the pathogens that pose a risk for wild carnivores in Central America, or whether domestic animals play a role in these risks.…”
Section: Introductionmentioning
confidence: 99%